The effect of masticatory behaviour on generalized attention in heathy volunteers. Issue 3 (27th December 2019) - Nagashima, Shintaro; Kimoto, Katsuhiko; Ono, Yumie; Ohno, Akinori; Hoshi, Noriyuki; Fuchigami, Kei; Manabe, Yuta
Abstract : Aim: As our society ages, the number of people living with dementia also steadily increases. Some work has focused on masticatory behaviour as a form of daily health care that could help prevent cognitive impairment and dementia. However, it is not yet clear how masticatory behaviour influences various cognitive functions. Therefore, the purpose of this study was to examine the effect of masticatory behaviour on the decline of generalized attention, an important cognitive function. Methods: Participants were 35 healthy, dentulous individuals without stomatognathic abnormalities (24 men, 11 women; mean age: 56.8 ± 4.8 years). All participants completed three interventions: mastication, foot‐stepping, and none (control). Pre‐ and post‐intervention measures of generalized attention were measured by using neuropsychological tests to examine general attention; the results were then compared. Simultaneously, during the generalized attention task, the functional activity of the prefrontal cortex was observed on functional near‐infrared spectroscopy. Results: Response time of generalized attention improved in both the masticatory and foot‐stepping interventions. There was a transient increase in oxyhaemoglobin activity in the right and left prefrontal cortices in the masticatory intervention. Conclusions: Masticatory behaviour may be involved in a partial improvement of generalized attention and may induce prefrontal cortex activity in middle‐aged and older adults.